Incidental Findings on Cone Beam Computed Tomography Images - Veeratrishul Allareddy; Steven D. Vincent; John W. Hellstein; Fang Qian; Wendy R. K. Smoker; Axel Ruprecht (Hindawi Limited, 2012)
Background. Cone beam computed tomography (CBCT) has gained widespread acceptance in dentistry for a variety of applications. Most dentists who are not radiologists/trained in radiology are generally not familiar with interpretation of anatomical structures and/or pathosis outside their area of primary interest, as often this was not within the scope of their training. Objectives. To assess that the number of incidental findings on a CBCT scan is high both within and outside of the primary area of interest, thereby emphasizing the importance of interpretation of all areas visualized on the scan. Materials and Methods. An oral and maxillofacial radiologist reviewed 1000 CBCT scans (382 males and 618 females) for findings both in- and outside the area of interest. Results. Of the 1000 subjects that were reviewed, 943 scans showed findings in the primary regions of interest and/or outside the regions of interest, and 76 different conditions were visualized in these scans both in and outside the areas of interest. Conclusion. From the wide scope of findings noted on these scans, it can be concluded that it is essential that a person trained in advanced interpretation techniques in radiology interprets cone beam computed tomography scans.